Activated surface for subsequent bonding

By actinic radiation activation of the surface of the plastic substrate that is difficult to bond, the problems of low bond strength and complex operation in traditional methods are solved, and efficient, safe and economical bonding effects are achieved.

CN115746372BActive Publication Date: 2025-04-15HENKEL KGAA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202211389030.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-10-10
Filing Date
2018-06-06
Publication Date
2025-04-15
Estimated Expiration
2038-06-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively bond plastic substrates such as PEEK, PPS, PARA and PEI, and traditional surface treatment methods have problems of safety, cost and operational complexity.

Method used

The surface is activated by exposing the surface of the plastic substrate to actinic radiation, such as ultraviolet rays, in a specific wavelength range, thereby increasing its bond strength to the adhesive. This method does not require the incorporation of activators or physical and chemical treatments.

Benefits of technology

Efficient bonding to difficult-to-bond plastic substrates is achieved, improving bond strength, simplifying operation, reducing costs, and eliminating safety risks in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115746372B_ABST
    Figure CN115746372B_ABST
Patent Text Reader

Abstract

A method for activating the surface of a plastic substrate formed from the following substances for subsequent bonding: (a) a polyaryletherketone, such as polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK); (b) a polymer containing a phenyl group directly attached to a carbonyl group, optionally wherein the carbonyl group is part of an amide group, such as polyarylamide (PARA); (c) polyphenylene sulfide (PPS); or (d) polyetherimide (PEI); the method comprises the step of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 700 nm; the energy of the actinic radiation to which the surface is exposed can be about 1.5 J / cm 2 To about 300J / cm 2 The more difficult to bond substrates can then be bonded more easily, for example using acrylic adhesives, epoxy adhesives or anaerobic adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application with international application number PCT / EP2018 / 064924, national application number 201880039483.2, and invention name “Activated surface for subsequent bonding” filed on June 6, 2018. Technical Field

[0002] The present invention relates to a method of activating a surface for subsequent bonding. Background Art

[0003] It is known in the adhesive industry that it is difficult to bond certain substrates (such as certain plastics). It is believed that at least one reason is the low surface energy / low surface tension properties of the plastic to be bonded. Adhesive compositions have been specially formulated for bonding such substrates. Additionally or alternatively, a primer has been used. The primer is applied to the substrate before the adhesive is subsequently applied in excess. Additionally or alternatively, surface treatments of the substrates have been used to make them easier to bond. Such treatments are typically due to physical effects, such as roughening the substrate surface, thereby making it easier to bond.

[0004] For example, to bond certain plastics, such as PEEK (polyetheretherketone); PPS (polyphenylene sulfide); polyaramid (PARA) or polyetherimide (PEI), various techniques have been used. PEEK is a difficult material to bond. PPS is also a difficult material to bond. The same is true for PARA and PEI.

[0005] Such plastic materials are often subjected to a surface treatment. Such surface treatment may be performed using chemical treatments such as etching, such as acid etching. It is also known to use physical grinding, such as sandblasting / grit blasting. Flame treatment and plasma techniques are also used. In each case, the treatment results in a physical change in the surface, which promotes better bonding.

[0006] It should be understood that chemical treatments such as acid etching are restrictive for commercial use for safety reasons. In addition, there are physical limitations in this process, such as application limitations to the plastics to be treated, for example, when treating the substrate with a chemical solution or immersing the substrate in a chemical solution, the process must be carefully controlled. The costs in terms of raw materials, processing and waste are also undesirable. In addition, it is usually not easy to carry equipment for carrying out this process. In addition, it is usually difficult to selectively process discrete areas to be bonded. Typically, it is unnecessary to process the surface area except the area to be bonded, and in some cases, all substrates are processed. This is unnecessary and wasteful.

[0007] Plasma technology requires large equipment. In addition to the capital cost, there are also challenges in terms of the size of the equipment, which makes it difficult to carry and use the equipment in, for example, confined spaces. Typically, plasma processes utilize one or more gases, which therefore need to be removed safely. This again means that there are physical limitations to the process and the area where the plasma treatment takes place must be carefully controlled.

[0008] It is reported that exposure of PEEK to UV / ozone will oxidize the surface, see (J. Mater. Chem., 1994, 4 (7), 1157). It is also reported that immersing a PEEK substrate in an acrylic acid solution and exposing the immersed PEEK to UV light forms an acrylic acid graft layer on the PEEK, see (Chem. RES. CHINESE UNIVERSITIES 2012, 28 (3), 542-545).

[0009] Physical abrasion can produce variable results, as it can be difficult to adequately control this method. In addition, there is often waste abrasive as a byproduct. Chemical activation can involve the use of chemicals, which can be dangerous if used incorrectly. If immersion is used, the entire substrate must be treated and not just the bonding area. Then, there may be handling issues associated with the treated substrate, as it is not possible to fix the untreated portion of the substrate.

[0010] While primers can be used to great effect, alternative methods of activating the surface for subsequent bonding are always required. This applies especially to PEEK, PARA, PPS or PEI, which tend to be difficult to bond plastics, so bond strengths are often lower than other plastics and this is often the case even when a primer is used.

[0011] Despite the existence of prior art proposed solutions to these problems, it would be desirable to provide alternative solutions so that end users have more available options. Summary of the invention

[0012] In all aspects of the invention, actinic radiation refers to actinic radiation from a light source that is specifically positioned to illuminate the substrates to be bonded, such as within 1 meter of the light source, such as within 30 cm of the light source. Thus, exposure refers to exposure to actinic radiation from such a light source and does not include ambient light (such as natural light, light from overhead lights, etc.).

[0013] When the substrate is treated prior to exposure to ultraviolet radiation, it is understood that the treated area of ​​the substrate is exposed to actinic radiation.

[0014] The present invention provides a method for activating the surface of a plastic substrate formed of:

[0015] (a) polyaryletherketones, such as polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK);

[0016] (b) polymers containing a phenyl group directly attached to a carbonyl group, optionally wherein the carbonyl group is part of an amide group, such as polyaromatic amide (PARA);

[0017] (c) polyphenylene sulfide (PPS); or

[0018] (d) polyetherimide (PEI);

[0019] The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 1000 nm;

[0020] The energy of the actinic radiation to which the surface is exposed is about 0.5 J / cm 2 To about 300J / cm 2 within the range.

[0021] Actinic radiation may include radiation having a wavelength within a range of about 200 nm to about 700 nm.

[0022] The energy of the actinic radiation to which the surface is exposed may be about 0.5 J / cm 2 About 240J / cm 2 within the range.

[0023] It will be appreciated that such energy exposure may be achieved in a relatively short period of time.

[0024] It will be appreciated that the methods of the present invention are applicable to substrates formed from these materials, including composite substrates, such as fiber reinforced substrates made from these materials, including carbon reinforced materials.

[0025] The method of the present invention does not require the incorporation of an activator into the plastic substrate. In this regard, it should be noted that in the past, activators that activate in response to actinic radiation (such as TiO2) have been incorporated into the substrate. Such activators are not necessary in the present invention.

[0026] The present invention does not require any of the above mentioned treatments to promote adhesion to produce physical changes to the surface, such as: chemical treatments, such as etching, such as acid etching; physical treatments, such as sandblasting / sandblasting; flame treatments; plasma treatments; ozone treatments, etc.

[0027] It should also be noted that the present invention works when only one of the two substrates to be bonded together is activated. When two substrates are to be bonded together, they can be identical, but each can be any of the following: PEEK, PEKK, PEK, PEEKK, PEKEKK, PARA, PPS or PEI.

[0028] The polyaryletherketone is desirably polyetheretherketone (PEEK) or polyetherketoneketone (PEKK). Suitable substrates for use in the present invention include: PEEK, PEKK, PARA, PPS or PEI.

[0029] It should be noted that references to the energy of actinic radiation in the present invention refer to the energy of actinic radiation experienced by / incident on a surface. This is different from the energy that may be emitted from a source.

[0030] The actinic radiation can be applied in any desired pattern. For example, the surface can be selectively exposed to actinic radiation to produce surface areas that are activated for subsequent bonding and surface areas that are not activated for subsequent bonding. A mask can be used that has areas that transmit actinic radiation to produce surface areas that are activated for subsequent bonding and areas that block actinic radiation to produce surface areas that are not activated for subsequent bonding.

[0031] It should be understood that for continuously moving production lines, for example, where continuous substrates pass through a light source to activate them, faster activation may be required. The duration of exposure may be from about 0.1 seconds to about 360 minutes, such as from about 0.5 seconds to about 180 minutes; for example, from about 0.5 seconds to about 30 minutes; including from about 3 seconds to about 19 minutes; optionally, less than about 240 seconds.

[0032] It has been found that the activation method is suitable for different substrates and for activating subsequent bonding with different adhesives. For example, activation can be performed for subsequent bonding with acrylic adhesives.

[0033] In the method of the present invention, the energy of the actinic radiation to which the surface is exposed can be about 3.5 J / cm 2 To about 100 J / cm 2 and / or the substrate may be PPS, PARA or PEI; and / or may be activated for subsequent bonding with an acrylic adhesive.

[0034] In the method of the present invention, the energy of the actinic radiation to which the surface is exposed can be about 2 J / cm 2 About 240J / cm 2within the range; and / or the substrate may be PEEK, PEKK, PEK, PEEKK, PEKEKK, PPS or PEI; and / or may be activated for subsequent bonding with an epoxy adhesive.

[0035] Activation can be performed for subsequent bonding with epoxy adhesives.

[0036] The method of the present invention may include the step of treating the surface with a (meth)acrylate prior to exposing the surface to actinic radiation. The (meth)acrylate may be selected from tetrahydrofurfuryl acrylate (THFA); methyl methacrylate (MMA); isobornyl acrylate (IBOA) and any combination thereof.

[0037] In the method of the present invention, the plastic substrate may be PPS; and / or may be activated for subsequent bonding with an acrylic adhesive; and / or the energy of the actinic radiation to which the surface is exposed may be about 25 J / cm 2 About 240J / cm 2 within the range.

[0038] The method of the present invention may include the step of treating the surface with copper acrylate prior to exposing the surface to actinic radiation.

[0039] In the method of the present invention, the energy of the actinic radiation to which the surface is exposed can be about 3 J / cm 2 About 240J / cm 2 within the range; and / or may be activated for subsequent bonding with an anaerobic adhesive.

[0040] Activation of the substrate may be performed for subsequent bonding with anaerobic adhesives.

[0041] The present invention also provides a method of bonding a first substrate to a second substrate, which method involves activating the first substrate according to the method of the present invention described herein, and then bonding the first substrate to the second substrate using an adhesive such as an acrylic adhesive, an epoxy adhesive or an anaerobic adhesive.

[0042] The bonding method of the present invention may include bonding a first substrate to a second substrate, wherein the first substrate is formed of:

[0043] (a) polyaryletherketones, such as polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK);

[0044] (b) polymers containing a phenyl group directly attached to a carbonyl group, optionally wherein the carbonyl group is part of an amide group, such as polyaromatic amide (PARA);

[0045] (c) polyphenylene sulfide (PPS); or

[0046] (d) polyetherimide (PEI);

[0047] The method comprises the following steps:

[0048] (i) exposing the surface of the first substrate to actinic radiation to activate the surface for subsequent bonding, wherein the actinic radiation comprises radiation with a wavelength in the range of about 10 nm to about 1000 nm; the energy of the actinic radiation to which the surface is exposed is about 0.5 J / cm 2 To about 300J / cm 2 Within the range,

[0049] (ii) Subsequently, the activated surface of the first substrate is bonded to the second substrate using an adhesive.

[0050] The method of bonding may include the step of treating the surface with copper acrylate prior to exposing the surface to actinic radiation.

[0051] The method of bonding may comprise the step of treating the surface with a (meth)acrylate prior to exposing the surface to actinic radiation.

[0052] In all aspects of the invention using actinic radiation, it is desirable that the duration of exposure is from about 0.1 seconds to about 360 minutes, such as from about 0.5 seconds to about 180 minutes; for example from about 0.5 seconds to about 30 minutes; including from about 3 seconds to about 19 minutes.

[0053] Shorter treatment times are desirable, so exposure times of 0.5 minute to less than about 12 minutes, 10 minutes, 8 minutes, 6 minutes, 4 minutes, 3 minutes, 2 minutes, or 1 minute are desirable. For example, optimal exposure can be achieved on such a time scale. In some cases, the time can be 20 seconds or shorter, for example 15 seconds or shorter, such as 10 seconds or shorter.

[0054] After exposure to (UV) radiation, the adhesive is applied and bonding occurs.

[0055] The present invention provides a method for activating the surface of a plastic substrate formed of: a polyaryletherketone, such as polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK);

[0056] The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 1000 nm;

[0057] Furthermore, the energy of the actinic radiation to which the surface is exposed is about 1.5 J / cm2 To about 40J / cm 2 for subsequent bonding with acrylic adhesives; or

[0058] The energy of the actinic radiation to which the surface is exposed is about 4 J / cm 2 About 850 J / cm 2 for subsequent bonding with epoxy adhesives.

[0059] The present invention provides a method for activating the surface of a plastic substrate formed of polyaromatic amide (PARA) for subsequent bonding.

[0060] The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 1000 nm; and

[0061] The energy of the actinic radiation to which the surface is exposed is about 10 J / cm 2 About 30J / cm 2 for subsequent bonding with acrylic adhesives.

[0062] The present invention provides a method for activating the surface of a plastic substrate formed of polyphenylene sulfide (PPS) for subsequent bonding.

[0063] The method comprises the steps of applying copper acrylate to the surface and then exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 1000 nm; and

[0064] The energy of the actinic radiation to which the surface is exposed is about 2 J / cm 2 About 240J / cm 2 for subsequent bonding with an acrylic adhesive, optionally wherein the surface is treated with a (meth)acrylate, such as tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), or isobornyl acrylate (IBOA), or any combination thereof, prior to exposing the surface to actinic radiation,

[0065] Alternatively, the surface is exposed to actinic radiation with an energy of about 5 J / cm 2 to about 312J / cm 2 for subsequent bonding with epoxy adhesives.

[0066] The present invention provides a method of activating a surface of a plastic substrate formed of polyaromatic amide (PARA) for subsequent bonding, the method comprising the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 1000 nm;

[0067] The energy of the actinic radiation to which the surface is exposed is about 10 J / cm 2 About 30J / cm 2 for subsequent bonding with acrylic adhesives.

[0068] The present invention provides a method for activating the surface of a plastic substrate formed of polyetherimide (PEI) for subsequent bonding.

[0069] The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of about 10 nm to about 1000 nm;

[0070] The energy of the actinic radiation to which the surface is exposed is about 3 J / cm 2 About 10J / cm 2 for subsequent bonding with acrylic adhesives.

[0071] Alternatively, the surface is exposed to actinic radiation with an energy of about 6 J / cm 2 To about 120J / cm 2 for subsequent bonding with epoxy adhesives.

[0072] The present invention provides a method for activating the surface of a plastic substrate formed of the following for subsequent bonding: a polyaryletherketone, such as polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK);

[0073] The method comprises the following steps:

[0074] Treat the surface with copper acrylate before exposing it to actinic radiation.

[0075] exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in a range of about 10 nm to about 1000 nm;

[0076] Furthermore, the energy of the actinic radiation to which the surface is exposed is about 9 J / cm 2 About 240J / cm 2 for subsequent bonding with anaerobic adhesives.

[0077] The present invention provides a method for activating the surface of a plastic substrate formed of polyaromatic amide (PPS) for subsequent bonding.

[0078] The method comprises the following steps:

[0079] Treat the surface with copper acrylate before exposing it to actinic radiation.

[0080] exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in a range of about 10 nm to about 1000 nm;

[0081] Furthermore, the energy of the actinic radiation to which the surface is exposed is about 14 J / cm 2 About 30J / cm 2 for subsequent bonding with anaerobic adhesives.

[0082] The present invention provides a method for activating the surface of a plastic substrate formed of polyaromatic amide (PARA) for subsequent bonding.

[0083] The method comprises the following steps:

[0084] Treat the surface with copper acrylate before exposing it to actinic radiation.

[0085] exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in a range of about 10 nm to about 1000 nm;

[0086] Furthermore, the energy of the actinic radiation to which the surface is exposed is about 10 J / cm 2 About 30J / cm 2 for subsequent bonding with anaerobic adhesives.

[0087] The present invention provides a method for activating the surface of a plastic substrate formed of polyetherimide (PEI) for subsequent bonding.

[0088] The method comprises the following steps:

[0089] Treat the surface with copper acrylate before exposing it to actinic radiation.

[0090] exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in a range of about 10 nm to about 1000 nm;

[0091] Furthermore, the energy of the actinic radiation to which the surface is exposed is about 3 J / cm 2 About 30J / cm 2 for subsequent bonding with anaerobic adhesives.

[0092] The present invention involves exposing the plastic samples to be bonded to the correct intensity of actinic radiation, such as UV radiation, for the desired time prior to applying the adhesive. After exposure to actinic (UV) radiation, the adhesive is applied and the substrates are bonded to one another.

[0093] The new method requires only at least one source of actinic radiation, such as a UV radiation source, and any radiation source can be small and easily portable. For example, it can be handheld and / or battery powered. Of course, although more powerful radiation sources can be used, these radiation sources can be powered by mains electricity.

[0094] Small or large areas can be treated as needed using different equipment (one or more point radiation sources to a large number of radiation sources). Only the area to be bonded needs to be exposed to the radiation. Thereafter, the substrate can be bonded to another substrate using an adhesive such as a standard two-component acrylic adhesive.

[0095] As shown in the following examples, the process of the present invention has been shown to work well with acrylic adhesives such as those sold under the trade name AA V5004 (acrylic adhesive) and HHD8540 (acrylic adhesive) adhesives for sale as well as various epoxy and anaerobic Products. All The products are all commercially available from Henkel Ireland Operation & Research Ltd, Tallaght, Dublin 24, Ireland. The acronym "AA" stands for acrylic adhesive. AAV5004 is a two component structural acrylic adhesive.

[0096] It will be appreciated that the method of the present invention requires only a source of (UV) radiation.

[0097] Using the method of the invention, it is easier to treat smaller areas, for example using a smaller radiation source, such as a UV source (such as a spotlight), or using an array of UV sources to treat a large area.

[0098] The invention has many advantages. Hazardous / expensive equipment and chemicals are eliminated. No wear and tear is required. The device is very portable and flexible.

[0099] The only health concern might be to prevent exposure to radiation (e.g. UV radiation). But this is easily controlled. For example, the user might have to use protective glasses to protect their eyes, or the radiation source might be shielded to protect the user. Also, there are no unwanted byproducts, such as ground plastic fragments, waste chemicals, used abrasive materials, exhaust, etc.

[0100] Therefore, the method of the present invention is very advantageous compared with the methods of the prior art.

[0101] Any suitable acrylate or methacrylate composition may be used. These include those based on acrylate or methacrylate components, including: methyl acrylate, methyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, isobornyl acrylate, isobornyl methacrylate, isooctyl acrylate, isooctyl methacrylate, acrylamide, n-methacrylamide, lauryl methacrylate and stearyl methacrylate, cyclohexyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate.

[0102] Other suitable acrylates or methacrylates are polyacrylates and polymethacrylates, as shown below:

[0103]

[0104] Wherein, R1 can be H or C1-C 20 Alkyl, suitably CH3, R2 can connect multiple monomer acrylate and / or methacrylate; wherein R2 can be selected from the group consisting of: C1-C 20 Alkyl, C2-C 20 Alkenyl, C3-C 20 Cycloalkyl, C3-C 20 The cycloalkyl group optionally has at least one C-C unsaturated bond, a C5-C 20 Aryl, C3-C 20Heteroaryl, carbamate, urea, glycol, ether, polyether or glycidyl components and combinations thereof, optionally substituted one or more times with at least one of hydroxyl, amino, halogen, cyano, nitro, C1-C5 alkoxy and / or C1-C5 thioalkoxy. n can be in the range of 2 to 4 (inclusive) acrylate units. Examples include: diethylene glycol diacrylate, diethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, tris(2-hydroxyethyl)isocyanurate trimethacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, and ethoxylated bisphenol diacrylates and dimethacrylates.

[0105] Suitable acrylate or methacrylate monomer units include methyl acrylate, methyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, stearyl methacrylate, isobornyl acrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, tetraethylene glycol diacrylate, tetraethylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, and the like.

[0106] The acrylate or methacrylate component may be present in an amount from about 10 wt % to about 95 wt % based on the total weight of the composition, desirably from about 20 wt % to about 85 wt % based on the total weight of the composition.

[0107] The acrylate or methacrylate composition may comprise a curable component, suitably a maleate, fumarate or maleimide component and combinations thereof. Examples include, but are not limited to, mono-2-(acryloyloxy)ethyl maleate, mono-2-(methacryloyloxy)ethyl maleate, maleic anhydride, maleic acid, maleic acid, fumaric acid, fumaramide, fumaronitrile, fumaryl chloride, zinc, calcium and magnesium fumarate monoethyl salts, 2,5-pyrroledione and 1,1'-(methylenebis-4,1-phenylene)bismaleimide, or combinations thereof.

[0108] The maleate, fumarate or maleimide curing agent component may be present in an amount of about 1 to about 20 weight % based on the total weight of the composition, suitably about 1.5 to about 10 weight % based on the total weight of the composition.

[0109] Some embodiments of the present invention can comprise toughening agent component.The example of toughening agent component comprises synthetic rubber, for example acrylonitrile / butadiene rubber (NBR rubber), polyurethane, styrene / butadiene rubber, styrene / butadiene / methacrylate rubber, chloroprene rubber or butadiene rubber, natural rubber, styrene thermoplastic elastomer, such as styrene / polybutadiene / styrene synthetic rubber, polyacrylate or polymethacrylate elastomer, methacrylate / acrylate block copolymer or olefin thermoplastic elastomer, such as polystyrene / EPDM (ethylene / propylene / conjugated diene copolymer) synthetic rubber.Also can use chlorinated and chlorosulfonated polyethylene elastomer.Toughening agent component can also be the mixture or dispersion of these types of materials.

[0110] The toughening agent component may be present in an amount of about 5 to about 50 weight percent based on the total weight of the composition, desirably present in an amount of about 10 to about 30 weight percent based on the total weight of the composition.

[0111] It is to be noted that when the inventors refer to a curable acrylate or methacrylate component, this includes any curable composition based on curing via an acrylate or methacrylate functional group, and specifically does not exclude combinations of acrylates and / or methacrylates or indeed components having more than one curable functional group.

[0112] It should also be understood that combinations of organoborane initiator components may be used. Combinations of activators of organoborane components may be used.

[0113] Such curable acrylate or methacrylate components are usually formulated as two-component compositions, where Part A and Part B are stored separately and then mixed for bonding.

[0114] When treating a surface with a (meth)acrylate, it is desirable to apply the liquid monomer directly to the surface.

[0115] When treating the surface with copper acrylate, a copper acrylate solution can be used. It can be easily applied to the surface of one or more plastic substrates, and then the plastic sample is exposed to the correct intensity of actinic (e.g., UV) radiation for the required time before applying the adhesive. After exposure, any excess solution can be removed, and the sample is then bondable to the adhesive.

[0116] Any suitable copper acrylate solution may be used, such as a solution of copper acrylate in: acrylic acid; 2-methyltetrahydrofuran; acetone; or water, or any combination thereof.

[0117] The invention is applicable to a variety of substrates and involves exposing the plastic sample to the correct intensity of actinic (eg UV) radiation for the required time prior to subsequent application of the adhesive.

[0118] Typically, standard anaerobic adhesives do not cure / bond well on plastics without a primer. While plastic primers are common and work well for subsequent bonding with anaerobic adhesives, primers generally work poorly on PEEK because it is a chemically stable plastic. The same is true for PEKK, PEK, PEEKK, PEKEKK, PARA, PPS, or PEI.

[0119] The method of the present invention is superior to known methods (eg, the use of a primer) because it achieves a desired bond strength to materials that are otherwise difficult to bond.

[0120] Any suitable anaerobically curable composition may be used for subsequent bonding.

[0121] Anaerobically curable compositions useful in the present invention include those wherein the anaerobically curable component is generally present in an amount from about 50 wt % to about 99 wt %, such as from about 55 wt % to about 95 wt %, of the total composition.

[0122] The curing component (for curing the anaerobic curable component) in the anaerobic curable composition may be present in an amount of about 0.1 to about 10 wt %, such as about 1 to about 5 wt %, for example about 5 wt %, based on the total weight of the composition.

[0123] Ideally, the anaerobic curable component includes a rubber component, such as a natural or synthetic rubber / elastomer component. The component may be present in an amount of about 5 to about 35 wt %, such as about 10 to about 35 wt %, for example about 15 to about 30 wt %, based on the total weight of the composition.

[0124] The anaerobic curable composition may have an anaerobically curable component based on a suitable (meth)acrylate component.

[0125] One or more suitable (meth)acrylate components may be selected from those having the following formula:

[0126] H2C=CGCO2R 8 ,

[0127] wherein G may be hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms, and R 8It can be selected from alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkaryl, aralkyl or aryl groups having 1 to about 16 carbon atoms, any of which can be optionally substituted or interrupted by silane, silicon, oxygen, halogen, carbonyl, hydroxyl, ester, carboxylic acid, urea, carbamate, polyurethane, carbonate, amine, amide, sulfur, sulfonate and sulfone.

[0128] One or more suitable (meth)acrylates may be selected from multifunctional (meth)acrylates, such as, but not limited to, difunctional (meth)acrylates or trifunctional (meth)acrylates, for example, polyethylene glycol di(meth)acrylate, tetrahydrofuran (meth)acrylate and di(meth)acrylate, hydroxypropyl (meth)acrylate ("HPMA"), hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate ("TMPTMA"), diethylene glycol dimethacrylate, triethylene glycol dimethacrylate ("TMPTA"),

[0043] Examples of the present invention include tetraethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, di(pentyl glycol) dimethacrylate, tetraethylene glycol diacrylate, diglyceryl tetramethacrylate, tetramethylene dimethacrylate, ethylene dimethacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, and bisphenol A mono- and di-(meth)acrylates, such as ethoxylated bisphenol A (meth)acrylate ("EBIPMA"), and bisphenol F mono- and di-(meth)acrylates, such as ethoxylated bisphenol F (meth)acrylate.

[0129] For example, the anaerobic curable component may include bisphenol A dimethacrylate:

[0130]

[0131] Other (meth)acrylates that may be suitable for use herein are silicone (meth)acrylate moieties ("SiMA") such as those taught and claimed in US Pat. No. 5,605,999 (Chu), the disclosure of which is expressly incorporated herein by reference.

[0132] Other suitable materials may be selected from polyacrylates represented by the following formula:

[0133]

[0134] Where R 4 is a group selected from hydrogen, halogen, or an alkyl group of 1 to about 4 carbon atoms; q is an integer equal to at least 1, preferably equal to 1 to about 4; and X is an organic group containing at least two carbon atoms and having a total bonding capacity of q plus 1. With respect to the upper limit of the number of carbon atoms in X, workable monomers exist essentially at any value. However, in practice, a typical upper limit is about 50 carbon atoms, such as desirably about 30 carbon atoms, and desirably about 20 carbon atoms.

[0135] For example, X can be an organic group of the formula:

[0136]

[0137] where Y 1 and Y 2 Each is an organic group, such as a hydrocarbyl group, containing at least 2 carbon atoms, and desirably 2 to about 10 carbon atoms, and Z is an organic group, preferably a hydrocarbyl group, containing at least 1 carbon atom, preferably 2 to about 10 carbon atoms. Other materials can be selected from the reaction products of di- or trialkanolamines (e.g., ethanolamine or propanolamine) and acrylic acid, such as disclosed in French Patent No. 1,581,361.

[0138] Suitable oligomers having (meth)acrylate functional groups may also be used. Examples of such (meth)acrylate functionalized oligomers include those having the general formula:

[0139]

[0140] Where R 5 represents a group selected from hydrogen, an alkyl group having 1 to about 4 carbon atoms, a hydroxyalkyl group having 1 to about 4 carbon atoms, or

[0141]

[0142] Where R 4 is a group selected from hydrogen, halogen or an alkyl group having 1 to about 4 carbon atoms; R 6 is a group selected from hydrogen, hydroxy, or

[0143]

[0144] m is an integer equal to at least 1, such as 1 to about 15 or more, desirably 1 to about 8; n is an integer equal to at least 1, such as 1 to about 40 or more, and desirably between about 2 to about 10; p is 0 or 1.

[0145] Typical examples of acrylate oligomers corresponding to the above general formula include diethylene glycol dimethacrylate, triethylene glycol dimethacrylate and tetraethylene glycol dimethacrylate. Di(pentylene glycol) dimethacrylate; tetraethylene glycol diacrylate; tetraethylene glycol di(chloroacrylate); diglycerol diacrylate; diglycerol tetramethacrylate; butanediol dimethacrylate; neopentyl glycol diacrylate; and trimethylolpropane triacrylate.

[0146] Although diacrylates and other polyacrylates, particularly those described in the preceding paragraph, may be desirable, monofunctional acrylates (esters containing one acrylate group) may also be used.

[0147] Suitable compounds may be selected from cyclohexyl methacrylate, tetrahydrofurfuryl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, tert-butylaminoethyl methacrylate, cyanoethyl acrylate and chloroethyl methacrylate.

[0148] Another class of useful materials are the reaction products of (meth)acrylate-functionalized hydroxyl- or amino-containing materials and polyisocyanates in appropriate proportions to convert all of the isocyanate groups to urethane or urea groups, respectively.

[0149] The (meth)acrylate urethane or urea thus formed may contain hydroxyl or amino functional groups on the non-acrylate portion thereof. Suitable (meth)acrylates for use may be selected from those of the following formula:

[0150]

[0151] wherein X is selected from -O- and

[0152] Where R 9 is selected from hydrogen or a lower alkyl group of 1 to 7 carbon atoms; R 7 is selected from hydrogen, halogen (such as chlorine) or alkyl (such as methyl and ethyl); and R 8 It is a divalent organic group selected from an alkylene group having 1 to 8 carbon atoms, a phenylene group and a naphthylene group.

[0153] These groups react appropriately with polyisocyanates to form monomers of the following general formula:

[0154]

[0155] wherein n is an integer from 2 to about 6; B is a polyvalent organic group selected from substituted and unsubstituted alkyl, alkenyl, cycloalkyl, cycloalkenyl, aryl, alkaryl, alkaryl and heterocyclyl, and combinations thereof; R 7 , R 8 and X have the meanings given above.

[0156] Depending on the nature of B, the molecular weight of these (meth)acrylates with urea or urethane linkages may place them in the oligomeric category (eg, about 1,000 g / mol to about 5,000 g / mol) or in the polymeric category (eg, about greater than 5,000 g / mol).

[0157] Other unsaturated reactive monomers and oligomers may be used, such as styrene, maleimide, vinyl ether, allyl, allyl ether and those mentioned in US6844080B1 (Kneafsey et al.). Vinyl resins mentioned in US6433091 (Xia) may also be used. Methacrylate or acrylate monomers containing these unsaturated reactive groups may also be used.

[0158] Of course, combinations of these (meth)acrylates and other monomers may also be used.

[0159] Desirably, the anaerobically curable component comprises at least one acrylate or methacrylate group.

[0160] Desirably, the anaerobic curable component comprises at least one member selected from the group consisting of epoxy (meth)acrylates, urethane (meth)acrylates, urethane di(meth)acrylates, alkyl (meth)acrylates, stearyl (meth)acrylates, isocyanurate (meth)acrylates, bisphenol A-(meth)acrylates, ethoxylated bisphenol A-(meth)acrylates, bisphenol F-(meth)acrylates, ethoxylated bisphenol-F-(meth)acrylates, bisphenol A di(meth)acrylates, ethoxylated bisphenol-A-di(meth)acrylates, bisphenol-F-di(meth)acrylates, and ethoxylated bisphenol-F-di(meth)acrylates.

[0161] The anaerobic compositions may also contain other conventional components, such as free radical initiators, free radical accelerators, inhibitors of free radical production, and metal catalysts, such as iron and copper.

[0162] Many well-known free radical polymerization initiators can be incorporated into the compositions of the present invention, including but not limited to hydroperoxides such as CHP, p-menthane hydroperoxide, t-butyl hydroperoxide ("TBH"), and t-butyl peroxybenzoate. Other peroxides include benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, diacetyl peroxide, 4,4-bis(t-butylperoxy)butyl valerate, p-chlorobenzoyl peroxide, cumene hydroperoxide, t-butylcumyl peroxide, t-butyl peroxybenzoate, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexane, 2,5-dimethyl-2,5-di-t-butylperoxyhex-3-yne, 4-methyl-2,2-di-t-butylperoxypentane, and combinations thereof.

[0163] Such peroxide compounds are generally used in the present invention in a range of about 0.1 to about 10 weight %, desirably about 1 to about 5 weight %, based on the total weight of the composition.

[0164] If desired, the initiator component can be encapsulated. For example, the initiator component can be an encapsulated peroxide, such as encapsulated benzoyl peroxide.

[0165] The composition used in the present invention may further comprise a thickener and / or a filler.

[0166] As mentioned above, it is understood that the compositions used in the present invention may include non-reactive materials (including resins). Such components do not participate in the anaerobic curing reaction. They are not reactive. However, during the curing process of other components, these components may become part of the cured product into which they are incorporated. Examples of such non-reactive materials include: fumed silica, polyethylene, polytetrafluoroethylene (PTFE), mica, polyamide wax, titanium dioxide, barium sulfate.

[0167] Standard 2K acrylic adhesives can be used to bond the substrates.

[0168] For example, the present invention may involve applying a (meth) acrylic monomer to the surface of a PPS substrate and then exposing the plastic sample to UV radiation of the correct intensity for the desired time before applying the adhesive. After UV exposure, the bond strength achieved with the acrylic adhesive to PPS is significantly stronger than the bond strength without UV activated primer. Note that for PPS, it is not necessary to introduce an activator such as TiO2 into the PPS substrate.

[0169] This method has been demonstrated to work with acrylic adhesives, e.g. AA V5004.

[0170] Therefore, the method of the present invention is very advantageous compared with the methods of the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0171] Figure 1 The adhesive strength test results of Example 14 are shown. DETAILED DESCRIPTION

[0172] For testing Method for samples of AA V5004 (acrylic adhesive)

[0173] Standard product (lap shears) size: 1 inch x 4 inches (2.54 cm x 10.16 cm) (width x length)

[0174] Overlap size: 1 / 4 inches [1 inch × 1 / 4 inches (2.54 cm x 0.635 cm) (width x length)]

[0175] The two-component adhesive ( AA V5004) was applied to the bonding area on one of the samples to be bonded.

[0176] The second sample has no adhesive applied directly to it. The bond areas of the overlap / test samples are aligned and the spring clips are used to 1 / 4 inch overlap and clamp them together. Allow the adhesive to cure for 24 hours at room temperature with the clamps. After the adhesive has cured, remove the clamps. Test by pulling in shear mode at a rate of 2 mm / min on a calibrated tensile testing machine until fracture. Strength is measured in MPa (N / mm 2 )Record.

[0177] For testing Method for samples of HHD8540 (acrylic adhesive)

[0178] Standard product (lap shear) size: 1 inch x 4 inches (2.54 cm x 10.16 cm) (width x length)

[0179] Overlap size: 1 / 4 inches [1 inch × 1 / 4 inches (2.54 cm x 0.635 cm) (width x length)]

[0180] The two-component adhesive ( HHD8540) is applied to the bonding area on one of the samples to be bonded.

[0181] The second sample has no adhesive applied directly to it. The bond areas of the overlap / test samples are aligned and the spring clips are used to 1 / 4 inch overlap and clamp them together. Allow the adhesive to cure for 24 hours at room temperature with the clamps. After the adhesive has cured, remove the clamps. Test by pulling in shear mode at a rate of 2 mm / min on a calibrated tensile testing machine until fracture. Strength is measured in MPa (N / mm 2 )Record.

[0182] For testing 5189 Anaerobic Adhesive Sample Method

[0183] Standard product (lap shear) size: 1 inch x 4 inches (2.54 cm x 10.16 cm) (width x length)

[0184] Overlap size: 1 / 4 inches [1 inch × 1 / 4 inches (2.54 cm x 0.635 cm) (width x length)]

[0185] Apply the one-component adhesive from a 50 ml bottle to one of the samples to be bonded without mixing.

[0186] The second sample has no adhesive applied directly to it. The bond areas of the overlap / test samples are aligned and the spring clips are used to 1 The adhesive was clamped together with an overlap of 1 / 4 inch. The adhesive was cured for 96 hours at room temperature using the clamps. After the adhesive cured, the clamps were removed. The test was conducted by pulling in shear mode at a rate of 2 mm / min on a calibrated tensile testing machine until fracture. Strength is measured in MPa (N / mm 2 )Record. 5189 is a liquid anaerobic composition for use as a flange sealant.

[0187] All bond strength tests were performed using standard procedure ASTM D3163. NOTE: All UV intensities were calibrated UV radiometer measurement, The measured UV bands are: UVC: 250-260nm, UVB: 280-320nm, UVA: 320-390nm and UVV: 395-445nm.

[0188] In all the following examples, all tests were performed using a grade of polyphenylene sulfide (PPS) that was injection molded. 6165PPS. In all the following examples, all tests used a grade of polyetherimide (PEI) which is TECAPEI. In all the following examples, all tests were performed using a grade of polyaramid (PARA) that was injection molded. 9950. In all the following examples, all tests used a grade of polyetheretherketone (PEEK) which is 450G is unreinforced semi-crystalline PEEK. In the case of the UVALOC 1000, a Mercury D-type bulb (doped with iron) was fitted. For example, it was used as the UV source in Examples 1, 2, 5, 6, 8, 9, 13, 15, 16, 17, 19 and 20, the intensity of which was measured using the calibrated PowerPuck described above. In other examples, a UV LED light source was used, as indicated.

[0189] Example 1: PEEK+UV for acrylic bonding

[0190] Do not UV treat the lap shears to be bonded. HHD8540 (acrylic adhesive) bonds unreinforced semi-crystalline PEEK (such as Victrex TM 450G PEEK) lap shear, the bond strength is 2.7MPa, at which the bond failure occurs.

[0191] In use The same PEEK lap shears were exposed to 110 mW / cm2 from a 375 nm LED lamp before bonding the lap shears with HHD8540 (acrylic adhesive). 2 After 1 min of UV irradiation, a significantly higher bond strength of 4.7 MPa was obtained, at which value bond failure again occurred.

[0192] Example 2: PEEK+UV for acrylic bonding

[0193] Do not UV treat the lap shears to be bonded. AA V5004 (acrylic adhesive) bonding unreinforced semi-crystalline PEEK (such as Victrex TM 450G PEEK) lap shear, the bond strength is 3.4MPa, at which the bond failure occurs.

[0194] In use The same PEEK lap shears were exposed to 375nm LED light @110mW / cm before bonding with AA V5004 (acrylic adhesive) 2 After 2 min of UV irradiation, a significantly higher bond strength of 7.8 MPa was obtained, at which value substrate failure occurred.

[0195] Unreinforced semi-crystalline PEEK (such as Victrex TM 450G PEEK) exposed to 375nm LED light @110mW / cm 2 The UV radiation for 4 minutes was used to obtain 4.4MPa of adhesive failure. Bond strength of V5004 (acrylic adhesive).

[0196] It should be noted that two exposure times (2 minutes and 4 minutes) achieved better results than no exposure to UV light. However, please note that the exposure can be optimized. For example, for any aspect of the present invention, an exposure time of about 10 seconds to about 2 minutes may be optimal.

[0197] Unreinforced semi-crystalline PEEK (such as Victrex TM 450G PEEK) exposed to UVALOC1000UV Cure Chamber UV radiation (UVA radiation @124mW / cm 2 、UVB radiation @109mW / cm 2 、UVC radiation @20mW / cm 2 and UVV radiation @76mW / cm 2 ) 2 minutes, the adhesive failure was 7.3MPa. Bond strength of AA V5004 (acrylic adhesive).

[0198] use AA V5004 bonding, in the unreinforced semi-crystalline PEEK (such as Victrex TM 450G PEEK using a 375nm LED handheld light source (33mW / cm 2 ), the bonding strength after exposure for 2 minutes was 4.5 MPa, and the bonding strength after exposure for 4 minutes was 4.1 MPa, both indicating adhesion failure.

[0199] Example 3: PARA UV for acrylic bonding

[0200] Without exposure to UV rays, AA V5004 (acrylic adhesive) bonded lap shears formed from 50% glass fiber reinforced polyaramid (PARA) (eg, Kalix 9950) and achieved a bond strength of 5.67 MPa, at which point bond failure was observed.

[0201] After exposure to 110 mW / cm from 375 nm LED light 2 After 2 minutes of UV radiation, AA V5004 (acrylic adhesive) bonded the same lap shears. A bond strength of 7.52 MPa was achieved, at which point bond failure was observed.

[0202] After exposure to 110 mW / cm from 375 nm LED light 2 After 4 minutes of UV radiation, AA V5004 (acrylic adhesive) bonded the same lap shears. A bond strength of 7.92 MPa was achieved, at which point bond failure was observed.

[0203] AA V5004 (acrylic adhesive) is a two-component methacrylate composition. HHD8540 is a two-component methacrylate composition.

[0204] Example 4: PEEK + Primer UV for anaerobic bonding

[0205] 5189 (anaerobic adhesive) does not bond to non-reinforced semi-crystalline PEEK (such as Victrex TM 450GPEEK) lap shears because the adhesive is not cured in the bondline.

[0206] The area to be bonded in each PEEK lap shear was treated with 1% (w / w) copper acrylate in acrylic acid, and the treated area of ​​the PEEK was subsequently exposed to a 375 nm LED lamp @115 mW / cm 2 UV radiation for 2 or 4 minutes, then remove the excess 1% copper acrylate solution in acrylic acid by wiping, and then use 5189 (anaerobic adhesive) bonded the lap shear materials and obtained bond strengths of 4.9MPa and 4.4MPa respectively, but both resulted in bond failure.

[0207] By comparison, a 1% copper acrylate solution in acrylic acid applied to the same type of PEEK lap shears, without exposing the treated surface to actinic radiation, achieved a bond strength of 2.52 MPa at bond failure.

[0208] Thus, this example shows that without pretreatment using copper acrylate or UV, bonding does not occur. It also shows that bonding occurs when pretreatment is applied.

[0209] Example 5: PEEK + Primer UV for anaerobic bonding

[0210] 5189 (anaerobic adhesive) does not bond to non-reinforced semi-crystalline PEEK (such as Victrex TM 450GPEEK) lap shears because the adhesive is not cured in the bondline.

[0211] Each PEEK lap shear region was treated with 1% (w / w) copper acrylate in acrylic acid and then exposed to UVALOC 1000UV Cure Chamber UV radiation (UVA radiation @124mW / cm 2 、UVB radiation @109mW / cm 2 、UVC radiation @20mW / cm 2 and UVV radiation @76mW / cm 2 ) for 30 seconds or 1 minute, then remove the excess 1% copper acrylate solution in acrylic acid by wiping, and then 5189 (anaerobic adhesive) bonded lap shears to achieve bond strengths of 7.0 MPa or 8.3 MPa, respectively, at bond failure.

[0212] Example 6: PEEK + Primer UV for anaerobic bonding

[0213] 5189 (anaerobic adhesive) does not bond to non-reinforced semi-crystalline PEEK (such as Victrex TM 450GPEEK) lap shears because the adhesive is not cured in the bondline.

[0214] Each PEEK lap shear region was treated with 3% (w / w) copper acrylate in 2-methyltetrahydrofuran and the treated PEEK was then exposed to UV radiation (@UVA: 213 mW / cm 2 、UVB:189mW / cm 2 、UVC:36mW / cm 2 、UVV:135mW / cm 2 ) for 2 or 4 minutes, and then the excess copper acrylate solution was removed by wiping, resulting in bond strengths of 5.3 MPa and 4.8 MPa (respectively) at bond failure.

[0215] A 3% copper acrylate solution in 2-methyltetrahydrofuran was applied and bonded to PEEK without prior UV exposure, yielding a bond strength of 0.89 MPa at adhesive failure.

[0216] Example 7: PEEK+primer UV for anaerobic bonding

[0217] 5189 (anaerobic adhesive) does not bond to non-reinforced semi-crystalline PEEK (such as Victrex TM 450GPEEK) lap shears because the adhesive is not cured in the bondline.

[0218] Each PEEK lap shear region was treated with 3% copper acrylate in acetone and then exposed to a 375 nm LED lamp @115 mW / cm 2 The films were irradiated with UV for 2 or 4 minutes, and then the excess copper acrylate solution was removed by wiping to obtain a bond strength of 3.5 MPa or 3.2 MPa (respectively) at bond failure.

[0219] PEEK was coated with 3% copper acrylate in copper acrylate and then exposed to 1W / cm2 of light from a 375nm LED lamp. 2The films were irradiated with UV for 2 or 4 minutes, and then the excess copper acrylate solution was removed by wiping to obtain bond strengths of 5.1 MPa and 4.1 MPa (respectively) at bond failure.

[0220] A 3% copper acrylate solution in acetone was applied and bonded to PEEK without prior UV exposure, yielding a bond strength of 0.96 MPa at bond failure.

[0221] Example 8: PARA+primer UV for anaerobic bonding

[0222] 5189 (anaerobic adhesive) does not bond to PARA (Kalix 9950) because the adhesive is not cured in the bondline.

[0223] 3% copper acrylate in 2-methyltetrahydrofuran was applied to the PARA, and the treated PARA was then exposed to UV radiation from a UV mercury lamp equipped with a D-type bulb (@UVA: 213 mW / cm 2 、UVB:189mW / cm 2 、UVC: 36mW / cm 2 、UVV:135mW / cm 2 ) for 2 or 4 minutes, and then the excess copper acrylate solution was removed by wiping to obtain bond strengths of 6.0 MPa and 8.1 MPa (respectively) at bond failure.

[0224] A 3% copper acrylate solution in 2-methyltetrahydrofuran was applied and bonded to PARA without prior UV exposure to obtain a bond strength of 5.5 MPa at adhesive failure.

[0225] Example 9: PPS + Primer UV for anaerobic bonding

[0226] No primer 5189 (anaerobic adhesive) did not bond to Fortran 6165 PPS and the adhesive was not cured in the bondline.

[0227] 3% copper acrylate in 2-methyltetrahydrofuran was applied to the PPS, and the treated PPS was then exposed to UV radiation (@UVA: 213 mW / cm 2 、UVB:189mW / cm 2 、UVC: 36mW / cm 2 、UVV:135mW / cm 2 ) for 2 or 4 minutes, and then the excess copper acrylate solution was removed by wiping, resulting in bond strengths of 5.2 MPa and 4.9 MPa (respectively) at bond failure.

[0228] A 3% copper acrylate solution in 2-methyltetrahydrofuran was applied and bonded to PPS without prior UV exposure to obtain a bond strength of 3.3 MPa at bond failure.

[0229] Example 10: PEEK + Primer UV for anaerobic bonding

[0230] No primer 5189 (anaerobic adhesive) does not bond to non-reinforced semi-crystalline PEEK (such as Victrex TM 450G PEEK) lap shears because the adhesive was not cured in the bondline.

[0231] 3% copper acrylate in water was applied to PEEK and the treated PEEK was then exposed to 115 mW / cm2 from a 375 nm LED lamp. 2 The films were irradiated with UV for 2 or 4 minutes, and then the excess copper acrylate solution was removed by wiping to obtain bond strengths of 3.1 MPa and 4.3 MPa (respectively) at bond failure.

[0232] A 3% copper acrylate solution in water was applied and bonded to PEEK without prior UV exposure, yielding a bond strength of 0.4 MPa at bond failure.

[0233] Example 11: PPS + UV primer for acrylic bonding

[0234] AA V5004 (acrylic adhesive) bonded PPS in a lap shear test and the adhesive failed at 7.4 MPa.

[0235] The same substrate was exposed to UV radiation (375 nm UV LED, 115 mW / cm 2 4 minutes) and then bonded using the same adhesive, the bond strength did not improve.

[0236] Areas of each PPS lap shear were treated with methacrylic acid and exposed for varying times to varying intensities of UV radiation from an LED light source at 375 nm. The following table shows the time, intensity, and bond strength achieved.

[0237]

[0238] These results indicate that the use of methacrylic primer alone improves the bond strength obtained, but the use of the correct amount (dose) of actinic radiation (such as UV) with methacrylic acid significantly improves the bond strength obtained using 2K acrylic adhesives on PPS. Assuming a minimum exposure to actinic radiation greater than 14 J / cm 2 , for example greater than about 15 J / cm 2, such as greater than about 17 joules / cm 2 , for example, greater than about 18 joules / cm 2 , such as greater than 19 joules / cm 2 , preferably greater than about 20 J / cm 2 .

[0239] The inventors believe that the drop in bond strength to 7.4 MPa and 8.9 MPa seen in the two results in the table above does indicate that a change (reaction) has occurred on the surface. Without being limited to any particular mode of action, it is believed that the change (reaction) needs to reach a certain state before the benefits of the combination of actinic radiation (such as UV) and methacrylic acid are seen. Therefore, exposure to actinic radiation for a sufficient period of time is required to see the benefits.

[0240] Example 12: PPS + UV primer for acrylic bonding

[0241] The PPS lap shear regions to be bonded were pretreated with *THFA, MMA, and IBOA, respectively, and then exposed to 1 W / cm2 of light from an LED light source at 375 nm. 2 The activated substrates were then exposed to UV radiation of varying intensities for different periods of time. AA V5004 (acrylic adhesive) bonding. The table below shows the materials used for pretreatment and the corresponding UV exposure time and the bond strength achieved.

[0242] Primer / Pretreatment* Average strength (MPa) Painted with THFA, no UV exposure 11.92 Paint with THFA and then expose to UV for 30 seconds 16.22 Paint with THFA and then expose to UV for 1 minute 13.34 Painted with MMA, no UV exposure 12.30 Paint with MMA and then expose to UV for 30 seconds 13.73 Paint with MMA and then expose to UV for 1 minute 15.81 Painted with IBOA, no UV exposure 12.46 Paint with IBOA and then expose to UV for 30 seconds 15.06 Paint with IBOA and then expose to UV light for 1 minute 18.17

[0243] These results indicate that the use of (meth)acrylate primers alone can improve the bond strength obtained, but the combination of UV and (meth)acrylates significantly improves the bond strength obtained using two-component acrylic adhesives on PPS.

[0244] *THFA: Tetrahydrofurfuryl acrylate; MMA: Methyl methacrylate; IBOA: Isobornyl acrylate

[0245] Example 13: PPS + Primer UV for Acrylic Bonding

[0246] The areas of the PPS lap shears to be bonded were pre-treated with IBOA and then bonded at the following strengths (by calibrating the Power Measurement) Exposure to UV from a mercury D-bulb for 30 seconds or 1 minute: 109 mW / cm 2 UVV (395-445nm), 184mW / cm 2 UVA (320-390nm), 169mW / cm 2 UVB (280-320nm) and 30mW / cm 2UVC (250-260nm). Then they were placed at room temperature for 2 weeks and then The following average bond strengths were obtained using AA V5004 (acrylic adhesive).

[0247] Exposure time 30 seconds: Bond strength 16.8MPa

[0248] Exposure time 1 minute: bonding strength 11.4 MPa.

[0249] These results show that priming effects can be achieved with actinic radiation (such as UV light of varying wavelengths) and that the resulting primed surfaces are stable for at least 2 weeks after priming. It also suggests that there is an optimum exposure. Thus, even if the bond strength after 1 minute is lower than after 30 seconds, there is still an overall positive effect on the bond strength after 1 minute.

[0250] Example 14: PPS + UV primer for acrylic bonding

[0251] The area of ​​the PPS lap shear to be bonded was treated with IBOA and then exposed to 1 W / cm2 from an LED light source at 375 nm. 2 The primer-coated substrates were then irradiated with UV radiation of 1000 nm for 1 minute. AA V5004 (acrylic adhesive). Some of the lap joints were tested first, and then some of the bonded items were aged for two weeks at 65°C / 95% relative humidity and 60°C dry conditions. In addition, some of the bonded lap joints were left at room temperature for the same period of time while the aging cycle was carried out. The results are shown in Figure 2. Figure 1 shown.

[0252] These results indicate that the priming process is stable to the aging cycles performed.

[0253] Example 15: PEEK UV for epoxy bonding

[0254] EA 9492 bonded to PEEK (Victrex 450G) without UV treatment, the adhesive failed at 4.5MPa. EA 9492 is a high temperature resistant two component epoxy adhesive.

[0255] The area to be bonded was exposed to the following UV radiation from a mercury D-type bulb for different times: UVA 193mW / cm 2 、UVB183mW / cm 2 、UVC 35mW / cm 2 、UVV 136mW / cm 2 , and we get the following results.

[0256] Exposure time (seconds) Bond strength (MPa) 75 8.26 90 9.46 105 10.06 120 11.33 135 12.38 150 8.17 165 6.71 180 8.00

[0257] These results suggest that with sufficient exposure, a significant increase in bond strength is observed, but too much exposure reduces this effect (although it is still better than no UV exposure at all).

[0258] Example 16: PEEK UV for epoxy bonding

[0259] EA9696 bonded to PEEK (Victrex 450G) without UV treatment, the adhesive failed at 4.5MPa. EA9696 is a modified epoxy film adhesive.

[0260] Expose the area to be bonded to UV radiation from a mercury D-type bulb for 130 seconds at: UVA 193 mW / cm 2 、UVB183mW / cm 2 、UVC 35mW / cm 2 、UVV 136mW / cm 2 , and a bonding strength of 11.45MPa was obtained.

[0261] EA9696 bonded to carbon fiber reinforced (CFR) PEEK (Tencate Cetex TC1200) without UV treatment, adhesive failure at 16.43 MPa. The area to be bonded was exposed to the following UV radiation from a mercury D-type bulb for 5 seconds: UVA 1801 mW / cm 2 、UVB 502mW / cm 2 、UVC 65mW / cm 2 、UVV 2322mW / cm 2 , a bond strength of 38.34 MPa was obtained, showing a mixed cohesive and adhesive failure mode.

[0262] Tests have shown that when this method is used to activate the surface of CFR-PEEK, bonding activity is maintained for at least 4 weeks.

[0263] Example 17: PEEK UV for epoxy bonding

[0264] EA9394 was bonded to PEEK (Victrex 450G) without UV treatment, and the adhesive failed at 3.4MPa. EA9394 is a two-component epoxy structural paste adhesive.

[0265] Expose the area to be bonded to UV radiation from a mercury D-type bulb for 130 seconds at: UVA 193 mW / cm 2 、UVB183mW / cm 2 、UVC 35mW / cm 2 、UVV 136mW / cm 2 , and a bonding strength of 8.8MPa was obtained.

[0266] EA9394 bonded to carbon fiber reinforced (CFR) PEEK (Tencate Cetex TC1200) without UV treatment, adhesive failure at 2.5 MPa. The area to be bonded was exposed to the following UV radiation from a mercury D-type bulb for 25 seconds: UVA 1801 mW / cm 2 、UVB 502mW / cm 2 、UVC 65mW / cm 2 、UVV 2322mW / cm 2 , a bonding strength of 29.86 MPa was obtained at adhesive failure.

[0267] Example 18: PEI and PPS UV for epoxy bonding

[0268] EA 9492 (epoxy adhesive) without UV treatment bonded to PEI with adhesive failure at 11.9 MPa, and bonded to PPS with adhesive failure at 12.2 MPa.

[0269] PEI was exposed to 1W / cm2 from a 375nm LED lamp. 2 UV radiation for 1 minute and EA 9492 (epoxy adhesive) bonded to obtain a bond strength of 19.5 MPa at substrate failure for PEI and a bond strength of 17.4 MPa at adhesive failure for PPS.

[0270] Example 19: PPS UV for epoxy bonding

[0271] EA 9492 (epoxy adhesive) bonded to PPS without UV treatment, and the adhesive failed at 12.2MPa.

[0272] PPS was exposed to UV radiation (UVA @ 213 mW / cm 2 、UVB@189mW / cm 2 、UVC@36mW / cm 2 and UVV: 135mW / cm2 ), measured using a calibrated PowerPuck, and EA9492 (epoxy adhesive) bonding, with structural failure of the substrate to obtain a bonding strength greater than 18MPa.

[0273] EA9394 (epoxy adhesive) bonded to carbon fiber reinforced (CFR) PPS (TencateCetex TC1100) without UV treatment, adhesive failure at 5.3 MPa. The area to be bonded was exposed to the following UV radiation from a mercury D-type bulb for 20 seconds: UVA 1653 mW / cm 2 、UVB 436mW / cm 2 、UVC 61mW / cm 2 、UVV 2275mW / cm 2 , a bonding strength of 39.0 MPa was obtained at adhesive failure.

[0274] EA9696 bonded to CFR PPS (Tencate Cetex TC1100) without UV treatment, adhesive failure at 8.17 MPa. The area to be bonded was exposed to the following UV radiation from a mercury D-type bulb for 10 seconds: UVA 1870 mW / cm 2 、UVB703mW / cm 2 、UVC 96mW / cm 2 、UVV 2548mW / cm 2 , a bond strength of 31.83 MPa was obtained, showing a mixed cohesive and adhesive failure mode. Increasing the time to 40 seconds at the same intensity resulted in a bond strength of 40.29 MPa with cohesive failure of the adhesive and structural failure of the substrate.

[0275] Tests have shown that when the surface of CFR-PPS is activated using this method, the bonding activity is maintained for at least 4 weeks.

[0276] Example 20: PPS UV for epoxy bonding

[0277] PPS lap shears were exposed to UV radiation (UVA @ 213 mW / cm 2 、UVB@189mW / cm 2 、UVC@36mW / cm 2 and UVV: 135mW / cm 2 ), through the calibrated PowerPuck TM Measure) for 1 minute.

[0278] These UV-activated PPS lap shears are used 9514 (one-component epoxy adhesive) bonding, with a bond strength of greater than 22 MPa achieved at 100% substrate failure. 9514 is a toughened, one component, heat curing epoxy adhesive.

[0279] Example 21: PPS and PEI UV for epoxy bonding

[0280] PPS and PEI lap shears were exposed to 115 mW / cm from a 375 nm LED flood light system. 2 UV radiation for 2 minutes.

[0281] Will use EA 9492 (epoxy adhesive) bonded UV activated PPS was exposed to ambient aging at 60°C (dry) and 65°C / 95% relative humidity for two weeks.

[0282] There was no significant change in bond strength, with a standard deviation of 20% from the initial strength, and all changes after aging were 10% below the original strength.

[0283] Use The same test was performed on UV activated PEI bonded with EA 9492 (epoxy adhesive).

[0284] There was no significant change in bond strength, with a standard deviation of 8% for initial strength and all changes after aging being 7% below the original strength.

[0285] Example 22: PEEK UV and acrylic monomers for 2K acrylic bonding

[0286] V5004 bonded to PEEK (Victrex 450G) without UV treatment, the adhesive failed at 3.4MPa.

[0287] The surface was brushed with methacrylic acid and the coated area was then exposed to 110 mW / cm2 of a 375 nm LED. 2 After 4 minutes of UV irradiation, a bonding strength of 7.1 MPa was obtained and substrate failure was observed.

[0288] Example 23: PEI UV for 2K acrylic bonding

[0289] V5004 bonded to PEI (Tecapei Ultem) without UV treatment, the adhesive failed at 5.3MPa.

[0290] The area to be bonded was exposed to 110 mW / cm from a 375 nm LED.2 The UV irradiation was continued for 30 seconds to obtain a bond strength of 6.4 MPa at adhesive failure.

[0291] The area to be bonded was exposed to 110 mW / cm from a 375 nm LED. 2 After 1 min of UV irradiation, a bond strength of 9.3 MPa was obtained at adhesive failure.

[0292] Example 24: PEI UV+Copper Acrylic for Anaerobic Bonding

[0293] No primer 5189 (anaerobic adhesive) does not bond to PEI (Tecapei Ultem) and the adhesive is not cured in the adhesive layer.

[0294] 1% copper acrylate in acrylic acid was applied to the PEI area to be bonded and the coated portion of the PEI was then exposed to light @115 mW / cm from a 375 nm LED lamp. 2 UV radiation for 30 seconds, 1 minute, 2 minutes or 4 minutes, and then remove the excess 1% copper acrylate solution in acrylic acid by wiping. When bonded with 5189 (anaerobic adhesive), bond strengths of 3.4 MPa, 3.4 MPa, 3.2 MPa and 4.7 MPa were obtained at adhesive failure (respectively).

[0295] Apply a 1% copper acrylate solution in acrylic acid without exposing the coated surface. When bonding with 5189 (anaerobic adhesive), a bonding strength of 2.0 MPa was obtained at adhesive failure.

[0296] Example 25: PEKK UV for epoxy bonding

[0297] EA9394 was bonded to PEKK without UV treatment, and the adhesive failed at 9.9MPa. EA9394 is a two-component epoxy structural paste adhesive.

[0298] In use Before bonding EA9394, the area to be bonded was exposed to 1W / cm2 of LED light at 375nm. 2 The UV radiation was applied for 60 seconds to obtain a bond strength of 30.8 MPa at adhesive failure.

[0299] The area to be bonded was exposed to 3.5 W / cm from a mercury D-type bulb. 2The bond strength was 34.6 MPa at adhesive failure. The area to be bonded was exposed to 3.5 W / cm2 of UV radiation from a mercury D-type bulb. 2 After 30 s of UV irradiation, the mixed adhesive and cohesive failure obtained a bond strength of 37.5 MPa.

[0300] When used herein for the present invention, the words "comprises / comprising" and the words "having / including" are used to specify the presence of stated features, integers, steps or components, but do not preclude the presence or addition of one or more other features, integers, steps, components or groups.

[0301] It should be understood that, for clarity, certain features of the present invention described in the context of separate embodiments may also be provided in combination in a single embodiment. On the contrary, for brevity, the various features of the present invention described in the context of a single embodiment may also be provided individually or in any suitable sub-combination.

Claims

1. A method for activating the surface of a plastic substrate formed of the following substances for subsequent bonding: (a) polyaryletherketone; (b) polymers containing a phenyl group directly attached to a carbonyl group, wherein the carbonyl group is part of an amide group; (c) polyphenylene sulfide (PPS); or (d) polyetherimide (PEI); The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of 200 nm to 445 nm; The surface is exposed to actinic radiation with an energy of 3.5 J / cm 2 Up to 300J / cm 2 within the scope of The method comprises the steps of treating the surface with only a (meth)acrylate prior to exposing the surface to the actinic radiation; The duration of the exposure is from 0.1 seconds to 30 minutes.

2. The method according to claim 1, wherein the (meth)acrylate is selected from tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), isobornyl acrylate (IBOA) and any combination thereof.

3. The method of claim 1 or 2, wherein the actinic radiation comprises radiation having a wavelength in the range of 250 nm to 445 nm.

4. The method according to claim 1 or 2, wherein: The surface is exposed to actinic radiation with an energy of 14 J / cm 2 Up to 240J / cm 2 within the range.

5. The method according to claim 1 or 2, wherein: Exposure of the surface to actinic radiation is applied selectively to produce surface areas that are activated for subsequent bonding and surface areas that are not activated for subsequent bonding.

6. The method of claim 5, wherein a mask is used, the mask having areas that transmit actinic radiation to create activated surface areas for subsequent bonding and areas that block actinic radiation to create non-activated surface areas for subsequent bonding.

7. The method according to claim 1 or 2, wherein: The energy of the actinic radiation to which the surface is exposed is 3.5 J / cm 2 Up to 100J / cm 2 to the extent that: and / or The substrate is polyphenylene sulfide (PPS), polyaromatic amide (PARA) or polyetherimide (PEI); and / or Activation is performed for subsequent bonding with acrylic adhesives.

8. The method according to claim 1 or 2, wherein: The energy of the actinic radiation to which the surface is exposed is 14 J / cm 2 Up to 240J / cm 2 to the extent that: and / or The substrate is polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK), polyetheretherketoneketone (PEEKK), polyetherketoneetherketoneketone (PEKEKK), polyphenylene sulfide (PPS) or polyetherimide (PEI); and / or Activation is performed for subsequent bonding with epoxy adhesive.

9. The method according to claim 1 or 2, wherein: The plastic substrate is polyphenylene sulfide (PPS); and / or The activation is performed for subsequent bonding with an acrylic adhesive; and / or The surface is exposed to actinic radiation with an energy of 25 J / cm 2 Up to 240J / cm 2 within the range.

10. The method according to claim 1 or 2, wherein: The surface is exposed to actinic radiation with an energy of 20 J / cm 2 Up to 240J / cm 2 to the extent that: and / or Activation is performed for subsequent bonding with anaerobic adhesives.

11. The method according to claim 1, wherein: The duration of the exposure is from 0.5 seconds to 30 minutes.

12. The method according to claim 1, wherein: The duration of the exposure ranged from 3 seconds to 19 minutes.

13. The method according to claim 1, wherein: The duration of the exposure is from 5 seconds to 240 seconds.

14. The method of claim 1 or 2, wherein the polymer containing a phenyl group directly attached to a carbonyl group is polyaromatic amide (PARA).

15. The method according to claim 1 or 2, wherein the polyaryletherketone is selected from polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK).

16. A method of bonding a first substrate to a second substrate, wherein the first substrate is formed of: (a) polyaryletherketone; (b) polymers containing a phenyl group directly attached to a carbonyl group, wherein the carbonyl group is part of an amide group; (c) polyphenylene sulfide (PPS); or (d) polyetherimide (PEI); The method comprises the following steps: (i) exposing the surface of the first substrate to actinic radiation to activate the surface for subsequent bonding, wherein the actinic radiation comprises radiation with a wavelength in the range of 200 nm to 445 nm; and the energy of the actinic radiation to which the surface is exposed is 3.5 J / cm 2 Up to 300J / cm 2 within the scope of (ii) subsequently, bonding the activated surface of the first substrate to the second substrate using an adhesive; The method comprises the steps of treating the surface with only a (meth)acrylate prior to exposing the surface to the actinic radiation; The duration of the exposure is from 0.1 seconds to 30 minutes.

17. The method according to claim 16, wherein the (meth)acrylate is selected from tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), isobornyl acrylate (IBOA), and any combination thereof.

18. The method of claim 16 or 17, wherein the polymer containing a phenyl group directly attached to a carbonyl group is polyaromatic amide (PARA).

19. A method of activating the surface of a plastic substrate formed from: polyaryletherketone; The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of 200 nm to 445 nm; Furthermore, the energy of the actinic radiation to which the surface is exposed is 3.5 J / cm 2 Up to 40J / cm 2 for subsequent bonding with an acrylic adhesive; or The energy of the actinic radiation to which the surface is exposed is 4 J / cm 2 Up to 850J / cm 2 within the range for subsequent bonding with epoxy adhesives; The method comprises the steps of treating the surface with only a (meth)acrylate prior to exposing the surface to the actinic radiation; The duration of the exposure is from 0.1 seconds to 30 minutes.

20. The method according to claim 19, wherein the (meth)acrylate is selected from tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), isobornyl acrylate (IBOA), and any combination thereof.

21. The method according to claim 16 or 19, wherein the polyaryletherketone is selected from polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK); polyetheretherketoneketone (PEEKK); or polyetherketoneetherketoneketone (PEKEKK).

22. A method for activating the surface of a plastic substrate formed of polyaromatic amide (PARA) for subsequent bonding, The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of 200 nm to 445 nm; and The energy of the actinic radiation to which the surface is exposed is 10 J / cm 2 Up to 30J / cm 2 within the range for subsequent bonding with acrylic adhesives; The method comprises the steps of treating the surface with only a (meth)acrylate prior to exposing the surface to the actinic radiation; The duration of the exposure is from 0.1 seconds to 30 minutes.

23. The method according to claim 22, wherein the (meth)acrylate is selected from tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), isobornyl acrylate (IBOA), and any combination thereof.

24. A method for activating the surface of a plastic substrate formed of polyphenylene sulfide (PPS) for subsequent bonding, The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of 200 nm to 445 nm; and The energy of the actinic radiation to which the surface is exposed is 3.5 J / cm 2 Up to 240J / cm 2 range, for subsequent bonding with acrylic adhesives, Alternatively, the energy of the actinic radiation to which the surface is exposed is 5 J / cm 2 Up to 312J / cm 2 within the range for subsequent bonding with epoxy adhesives; The method comprises the steps of treating the surface with only a (meth)acrylate prior to exposing the surface to the actinic radiation; The duration of the exposure is from 0.1 seconds to 30 minutes.

25. The method according to claim 24, wherein the (meth)acrylate is selected from tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), isobornyl acrylate (IBOA), and any combination thereof.

26. A method for activating the surface of a plastic substrate formed of polyetherimide (PEI) for subsequent bonding, The method comprises the steps of exposing the surface to actinic radiation, wherein the actinic radiation comprises radiation having a wavelength in the range of 200 nm to 445 nm; The energy of the actinic radiation to which the surface is exposed is 3.5 J / cm 2 Up to 10J / cm 2 range, for subsequent bonding with acrylic adhesives, Alternatively, the energy of the actinic radiation to which the surface is exposed is 6 J / cm 2 Up to 120J / cm 2 within the range for subsequent bonding with epoxy adhesives; The method comprises the steps of treating the surface with only a (meth)acrylate prior to exposing the surface to the actinic radiation; The duration of the exposure is from 0.1 seconds to 30 minutes.

27. The method according to claim 26, wherein the (meth)acrylate is selected from tetrahydrofurfuryl acrylate (THFA), methyl methacrylate (MMA), isobornyl acrylate (IBOA), and any combination thereof.

Citation Information

Patent Citations

  • FR1581361A

  • Anaerobically curable silicones

    US5605999A

  • Adhesive composition

    US6433091B1

  • Metal alkyl borphydride polymerisation initiators, polymerisable compositions, and uses thereof

    US6844080B2

  • Heat-resistant adhesive sheet

    CN101479356A